Examining the relationship among quality assurance, strategic leadership and school-based management towards school effectiveness in the Islamic private secondary schools in Southern Thailand - Himphinit, Musakkid (Kulliyyah of Education, International Islamic University Malaysia, 2018)
The purpose of this study is to examine the relationship between quality assurance and strategic leadership moderated by school-based management towards school effectiveness in the Islamic private secondary schools in Southern Thailand. The quality assurance (QA) and strategic leadership (SL) theory are measured and assessed through the school-based management (SBM) on school effectiveness (SE). The study selects 605 school teachers to complete questionnaire survey out of 683 targeted distribution from Islamic private secondary schools in Southern Thailand. The statistical techniques employed in this study include Descriptive Statistics using SPSS version 19, Confirmatory Factor Analysis (CFA) and full-fledged Structural Equation Modelling (SEM) with software Analysis of Moment Structures (AMOS) version 20.1 to addresses the research questions and to the test the research hypotheses. This research finds that Quality Assurance and Strategic Leadership are moderated by School-Based Management on School Effectiveness as perceived by teachers. Further analysis shows that School-Based Management has a direct causal effect on School Effectiveness. Theoretically, the study finds that School-Based Management positively influences the Islamic private secondary schools to be effective schools. There are implications for the study which the Ministry of Education should embrace. As this is the current research of educational management in Thailand, Quality Assurance, Strategic Leadership and School-Based Management are some important strategies that reflect the Ministry of Education's policy to enhance the quality of education particularly in the Southern Thailand. This study also recommends more research on the additional underlying constructs to authenticate the developed model of school effectiveness.